Callous-Unemotional Traits and Face-Emotion Recognition as Mediators in Conduct Problems of Children With ADHD. (October 2022) - Levy, Tomer; Peskin, Miriam; Kohn, Yoav; Sheinhorn, Sapir; Schoen, Gila; Weizman, Abraham; Golubchik, Pavel
Background: Attention-deficit/hyperactivity disorder (ADHD) is associated with increased risk for conduct problems (CP), as well as with callous-unemotional traits (CUt) and lower accuracy in face emotional recognition (FER). It is unclear, however, whether CUt and low accuracy in FER contribute to the risk for CP in ADHD. The present study investigated the possibility of such contribution. Methods: This pilot study's participants included 31 children aged 7–17 years, diagnosed with ADHD, and treated in a psychiatric outpatient clinic. The parents rated their children on the ADHD Rating Scale, Inventory of Callous-Unemotional Traits, and the Child Behavior Checklist-Conduct Problems scale. Participants completed the Hebrew version of the children's Reading the Mind in the Eyes Test (cRMET)—a Theory of Mind measure. A bootstrapped multiple mediator model was used, adjusting for age and gender. Results: ADHD symptoms were associated with CP. This association was not mediated by CUt or cRMET. CUt was associated with CP independent of ADHD symptom severity. Conclusions: ADHD symptoms and CUt both should be considered when assessing risk for CP and devising a treatment plan, in children with ADHD. Current results did not confirm the hypothesis that cRMET and CUt mediate between ADHD symptoms and CP. More studies employing larger samples, longitudinal design, and other emotion recognition measures are needed.